Alliances : an Executive Guide to Designing Successful Strategic Partnerships - De Man, Ard-Pieter. (Hoboken : Wiley, 2013)
A timely and practical guide that helps senior managers design successful strategic partnerships Strategic alliances are increasingly common among modern corporations and a hot topic in today's business schools. Alliance is a sophisticated guide to crafting successful partnerships, offering a combination of carefully designed checklists, up-to-date examples and scenarios from around the world, and the tools needed to ensure that all elements of an alliance are taken into account and fully assessed. Most managers don't have the experience or knowledge to create a functional alli.
Strategic alliances: The control-trust dilemma -- The Alliance Design Framework -- Turning suppliers into allies -- Contractual alliances: The customization of alliance design -- The virtual joint venture model: Air France/KLM, Delta Airlines, and Alitalia -- Equity alliances and joint ventures -- Multi-partner alliances: The more the merrier? -- Managing the dynamics: Mutual adjustment and continuous negotiation -- Designing and implementing strategic alliances: Art, science, and craft -- Open alliances: Towards the third generation of collaboration -- Appendix: Financial models behind alliances.
Includes index.
Includes bibliographical references at the end of each chapters and index.
Print version record.
Keywords: Strategic alliances (Business); Business; Strategic alliances (Business); Strategic partnerships; Strategic alliances (Business); Electronic books